The silent burden: a landscape analysis of common perinatal mental disorders in low- and middle-income countries - Shanon E McNab; Sean L Dryer; Laura Fitzgerald; Patricia Gomez; Anam M. Bhatti; Edward Kenyi; Aleefia Somji; Neena Khadka; Suzanne Stalls (BMC, 2022)
Abstract Background Mental health has long fallen behind physical health in attention, funding, and action-especially in low- and middle-income countries (LMICs). It has been conspicuously absent from global reproductive, maternal, newborn, child, and adolescent health (MNCAH) programming, despite increasing awareness of the intergenerational impact of common perinatal mental disorders (CPMDs). However, the universal health coverage (UHC) movement and COVID-19 have brought mental health to the forefront, and the MNCAH community is looking to understand how to provide women effective, sustainable care at scale. To address this, MOMENTUM Country and Global Leadership (MCGL) commissioned a landscape analysis in December 2020 to assess the state of CPMDs and identify what is being done to address the burden in LMICs. Methods The landscape analysis (LA) used a multitiered approach. First, reviewers chose a scoping review methodology to search literature in PubMed, Google Scholar, PsychInfo, and Scopus. Titles and abstracts were reviewed before a multidisciplinary team conducted data extraction and analysis on relevant articles. Second, 44 key informant interviews and two focus group discussions were conducted with mental health, MNCAH, humanitarian, nutrition, gender-based violence (GBV), advocacy, and implementation research experts. Finally, reviewers completed a document analysis of relevant mental health policies from 19 countries. Results The LA identified risk factors for CPMDs, maternal mental health interventions and implementation strategies, and remaining knowledge gaps. Risk factors included social determinants, such as economic or gender inequality, and individual experiences, such as stillbirth. Core components identified in successful perinatal mental health (PMH) interventions at community level included stepped care, detailed context assessments, task-sharing models, and talk therapy; at health facility level, they included pre-service training on mental health, trained and supervised providers, referral and assessment processes, mental health support for providers, provision of respectful care, and linkages with GBV services. Yet, significant gaps remain in understanding how to address CPMDs. Conclusion These findings illuminate an urgent need to provide CPMD prevention and care to women in LMICs. The time is long overdue to take perinatal mental health seriously. Efforts should strive to generate better evidence while implementing successful approaches to help millions of women "suffering in silence."